2020
DOI: 10.3390/ijerph17218193
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter (PM2.5) from Biomass Combustion Induces an Anti-Oxidative Response and Cancer Drug Resistance in Human Bronchial Epithelial BEAS-2B Cells

Abstract: Nearly half of the world’s population relies on combustion of solid biofuels to cover fundamental energy demands. Epidemiologic data demonstrate that particularly long-term emissions adversely affect human health. However, pathological molecular mechanisms are insufficiently characterized. Here we demonstrate that long-term exposure to fine particulate matter (PM2.5) from biomass combustion had no impact on cellular viability and proliferation but increased intracellular reactive oxygen species (ROS) levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…Consistent with other reports (An et al, 2014;Delgado & Ribeiro-Varandas, 2015;Huang et al, 2020;LaPensee et al, 2009LaPensee et al, , 2010Li et al, 2019;Merk et al, 2020;Nair et al, 2020;Ramos et al, 2019;Sonavane et al, 2018), the pollutants tested here were only able to significantly reduce the cytotoxic effects of the chemotherapy drug when exposure occurred earlier. This would indicate that pollutants need to activate evasion mechanisms before cells face cytotoxic effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other reports (An et al, 2014;Delgado & Ribeiro-Varandas, 2015;Huang et al, 2020;LaPensee et al, 2009LaPensee et al, , 2010Li et al, 2019;Merk et al, 2020;Nair et al, 2020;Ramos et al, 2019;Sonavane et al, 2018), the pollutants tested here were only able to significantly reduce the cytotoxic effects of the chemotherapy drug when exposure occurred earlier. This would indicate that pollutants need to activate evasion mechanisms before cells face cytotoxic effects.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, cotreatments in esophageal cancer cells with benzo( a )pyrene (BaP) (10 μM) and CDDP (4.2 μM), 5‐fluorouracil (5‐FU; 3.5 μM), or paclitaxel (PTX; 2 μM) for 24 h caused a decrease in apoptosis (Dzobo et al, 2018). Meanwhile, in BEAS‐2B cells, which are bronchial epithelial cells transformed with Ad12‐SV40 2B virus, prolonged exposure to fine particulate matter (PM 2.5 ) was found to decrease the cytotoxic effects of DOX by preventing its intracellular accumulation (Merk et al, 2020). Pretreatment for 24 h with low doses of polychlorinated biphenyls (PCB‐1254; 1 μg/ml) or hexabromocyclododecane (HBCD; 1 μM), two persistent organic pollutants (POPs), followed by combined treatment of either of these compounds and CDDP (10 μM) for an additional 24 h reduced chemotherapy‐mediated cell death by at least 5% in hepatocellular carcinoma (HCC) cells (An et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Volatile anesthetics associate with multiple and selective sites on human serum albumin [16] and promote cellular disturbance characteristic of more conventional chemical carcinogens: oxidative stress, mitochondrial dysfunction and chemoresistance [17] [18]. Anesthetic inhibition of the P-glycoprotein ATPase and drug efflux from MDR proteins in cell cultures occurs via membrane fluidization and not through conventional inhibition of enzyme activity [19].…”
Section: Discussionmentioning
confidence: 99%
“…In BEAS-2B cells transformed with Ad12-SV40 2B, it was found that prolonged exposure (5 weeks) to fine particles of 2.5 μm or smaller (PM2.5, biomass combustion product) decreases the cytotoxic effects of DOX (1 μM) by preventing its intracellular accumulation. This phenomenon was related to an increase in GSH levels and a consequent up-regulation of the drug efflux transporter MRP2 (which uses GSH conjugates as a substrate) [ 20 ]. Another aspect that could also be collaborating to generate chemoresistance is that chronic exposure to PM2.5 promotes an increase in cells with properties of cancer stem cells (CSCs) through the activation of the Notch signaling pathway and changes in the levels of stemness-associated miRNAs [ 92 , 93 ].…”
Section: Evidence Of Pollutants Affecting the Efficacy Of Chemotherap...mentioning
confidence: 99%